Pengembangan Pendidikan Karakter Program Kampus Mengajar Pada Siswa Kelas V di UPT SPF SD Negeri Tabaringan 5 Kabupaten Ujung Tanah Kota Makassar - Hijrah Hijrah; Badruddin Kaddas; Erwin Nurdiansyah; Ince Prabu Setiawan; Erniati Erniati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The aim of the researcher in this study is to determine the development of character education in fifth grade students. This research method uses qualitative methods. This type of research is a case study with a qualitative design. The results of the study indicate that the fifth grade students' character education development is not optimal. Three indicators of character education in this study are religious, discipline, and responsibility. These three indicators of character education have not been fully implanted in the personality of grade 5 students, such as 1) religious: ethics in praying before and after learning are still playing around and some have not memorized the prayer study. 2) discipline: there are still students who are late for class, don't collect assignments on time, and litter. 3) responsibility: not maintaining cleanliness, not doing assignments, and not carrying out assigned class picket assignments.